Impaired performances with excessive high-intensity free-weight training - Fry, A. C.; Webber, J. M.; Weiss, L. L.; Fry, M. D.; Li, Y. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to determine if 3 weeks of high relative intensity (percent one repetition maximum [1RM]) free-weight resistance training using the parallel barbell squat results in overtraining and to determine what types of performance would be affected. Six weight-trained males ( ± SD; age = 27.5 ± 5.4 year) trained 2 d·wk1 for 4 weeks with a normal protocol (Monday, 3 × 10 repetition maximum [RM]; Thursday, 3 × 5 RM), followed by 3 weeks of high-intensity training 3 d·wk1 (Monday, Wednesday, Friday) using 2 × 1 95% 1RM and 3 × 1 90% 1RM. A time-series study design was utilized, with each subject serving as his own control (pretest [Pre] test 1 = normal training; tests 1-4 = high-intensity training; test 4 posttest [Post] = recovery). One repetition maximum increased (p < 0.05) during normal training but did not change during high-intensity or recovery training (Pre = 139.5 ± 29.9 kg; test 1 = 154.6 ± 27.7 kg; test 2 = 160.3 ± 26.9 kg; test 3 = 163.7 ± 27.9 kg; test 4 = 161.0 ± 27.2 kg; Post = 161.7 ± 33.3 kg). Muscular and joint pain and soreness were not evident according to self-report training questionnaires. Also during the high-intensity phase, sprint times for 9.1 m increased (test 1 = 1.75 ± 0.12 seconds; test 4 = 1.86 ± 0.12 seconds) and peak isokinetic squat force at 0.20 m·s1 decreased (test 1 = 2,473.2 ± 685.6 N; test 4 = 2,193.3 ± 534.5 N). In general, no changes were observed for body composition, flexibility, lower body reaction time, vertical jumps, 36.6-m sprints, lateral agility, isokinetic squat force at 0.82 and 1.43 m·s1, or isokinetic back extension at 0.17 and 1.05 rad·s1. Although use of single repetitions at a high relative intensity is often used to increase 1RM, this was not observed in the present study. While 1RM performance did not decrease, other performance measures were adversely affected, suggestive of an excessive use of high relative intensity resistance exercise.